Antimicrobial compounds from Rhizophora stylosa - Huong, Phan Thi Thanh; Thanh, Nguyen Van; Diep, Chau Ngoc; Thao, Nguyen Phuong; Cuong, Nguyen The; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Minh, Chau Van (Vietnam Journal of Science and Technology, 2015)
(6S,7E,9R)-6,9-dihydroxy-4,7-megastiymadien-3-one 9-O-[α-L-arabinopyranosyl-(l→6)-β-D-glucopyranoside] (1), blumenol A (2), and kaempferol 3-rutinoside (3) were isolated from the methanol extract of the leaves of mangrove plant Rhizophora stylosa Griff. Structural elucidation of the metabolites was carried out by analysis of their spectroscopic data and by comparison with those reported in the literature. All these compounds exhibited antimicrobial activity and were isolated from this genus for the first time.